The Profile of COVID-19 Patients in Semen Padang Hospital Indonesia - Fauzar, Fauzar; Kurniati, Roza; Abdullah, Farhan; Kam, Alexander (Faculty of Medicine, Universitas Andalas, 2021)
The rapid increase in the number of Coronavirus Disease 2019 (COVID-19) cases, including in Padang, has led the government to designate several hospitals as referrals for COVID-19 patients. The profile of COVID-19 patients is needed to describe the pattern of this disease in Padang. Objectives: To revealed the profile of COVID-19 patients in SPH, Indonesia. Methods: This was a retrospective study. This study was conducted and collected data of COVID-19 patients from March to June 2020. Results: There are 54 patients with mean age of 50.93 (14.6) years old, 43% male and 57% female. The clinical manifestations are cough (74%), fever (37%), sore throat (22%), and fatigue (35%). There are 82% of patients admitted that they have contacted with other COVID-19 patients or have activities in COVID-19 cluster area, and only 7% have traveled to other cities. The mean length of stay is 31.91 (14.87) days. The mean laboratory data: Hemoglobin 13.7 (1.39) gr/dl, WBC 8,037.04 (2,846.27) /mm3, platelet 274,389 (75,053.80) /mm3, and NLR 3.16 (3.37). Chest radiograph results are bronchopneumonia (22.22%), cardiomegaly (7.41%), and normal (70.37%). Conclusion: The profile of COVID-19 patients in SPH is more in female patients, cough is the most clinical manifestation that appeared, the mean laboratory data (hemoglobin, WBC, and platelet) are normal, and normal chest radiography is the most chest radiograph results in these patients.Kata kunci: COVID-19, Padang, profile